Protein intake and dietary glycemic load of 4-year-olds and association with adiposity and serum insulin at 7 years of age: sex-nutrient and nutrient–nutrient interactions - Durão, C (2017)
BACKGROUND/OBJECTIVES: The role of Protein Intake (PI) at preschool age on later adiposity is understudied, and prospective studies also examining Dietary Glycemic Load (GL) are lacking. The current study evaluated the association of PI and GL at 4 years with adiposity and Fasting Serum Insulin (FSI) 3 years later, and examined the possible interaction between PI and GL on these associations, by sex. DESIGN: This prospective study included 1999 singleton children enrolled in the population-based birth cohort, Generation XXI (Porto, Portugal, 2005–2006). Diet at 4 years was assessed by 3-days food diaries. Energy-adjusted PI and GL (g per day) were converted into sex-specific tertiles (T). At 7 years, Body Mass Index (BMI) z-scores were defined according to the World Health Organization. Sample’s sex-specific z-scores were computed for Fat Mass Index (FMI), Waist-to-Height ratio (W/Ht) and FSI. Associations were estimated by linear regression coefficients (β) and 95% confidence intervals (95% CI). RESULTS: After adjustment for confounders, PI was positively associated with BMI in girls (T2 vs T1: β = 0.187; 95% CI: 0.015, 0.359) and boys (T3 vs T1: β = 0.205; 95% CI: 0.003, 0.406), being associated with FSI only in boys (T3 vs T1: β = 0.207; 95% CI: 0.011, 0.404; P-interaction = 0.026). Also, GL was associated with BMI only in boys (T3 vs T1: β = 0.362; 95% CI: 0.031, 0.693; P-interaction = 0.006), in whom significant interactions between PI and GL were found on the association with FMI (P = 0.019) and W/Ht (P = 0.039). Boys within the third T of both PI and GL at 4 years had higher FMI (β = 0.505; 95% CI: 0.085, 0.925) and W/Ht (β = 0.428; 95% CI: 0.022, 0.834) at 7 years. CONCLUSIONS: In both girls and boys, PI at preschool age is positively associated with later BMI, being positively associated with FSI only in boys. Dietary GL is associated with adiposity only in boys, in whom it seems to interact with PI enhancing increased adiposity.